Academician perceptions towards online student evaluation - Nor Hapiza Mohd Ariffin; Siti Nor Hidayah Askol (Institute of Advanced Engineering and Science, 2019)
In higher education institutions, student evaluation is important to ensure that students are given the opportunity to attain a high quality of education. In Universiti Teknologi Mara (UiTM) Malaysia, student evaluation was implemented through a system called Student Feedback Online (SuFO). This study aims to investigate and analyze the perception of academicians towards the usage of online student evaluation using SUFO in UiTM. The research employed the quantitative analysis and supported by Rasch measurement. The respondents are academicians in UiTM Shah Alam. A total of 152 academicians responded to the questionnaires. By using a Likert scale, 25 items were designed in the questionnaire and distributed by official email to the academicians. Data were analyzed using Rasch measurement to measure the validity and reliability of the items and the respondents involved in this research, while SPSS was used to analyze the quantitative data. The results showed that the academicians accepted the outcome value of student evaluation and they agreed that results of student evaluation should be used for formative assessment. It is recommended for future research, an instrument using a method of multi-dimensional evaluation of teaching should be developed to evaluate the effectiveness of university teaching.